Diagnostic difficulties in the detection of spinal osteoblastoma in a child - Skuza, Małgorzata; Stachowicz-Stencel, Teresa (Pediatria Polska - Polish Journal of Paediatrics, 2018)
We describe a case of a 15-year-old boy with low back pain that progressed and subsequently developed into unilateral lower limb numbness. An X-ray study was inconclusive, but a CT study showed a vertebral body mass with intravertebral space narrowing. An additional MRI study displayed compression of the spinal roots. The child demanded surgical management. A histological examination from the excised tumour revealed osteoblastoma.